Peningkatan Hasil Belajar Matematika Siswa Dengan Menggunakan Media Gambar Pada Materi Menentukan Sudut di SDN 009 Bengkong Kota Batam - Heldanis, Parida (Universitas Muhammadiyah Magelang, 2021)
The purpose of this study was to improve mathematics learning outcomes through media images for students at SDN 009 Bengkong, Batam City. By using an attractive learning model, it can affect the results of the learning process in the classroom. The value of mathematics subjects at SDN 009 Bengkong still has low learning outcomes. During the learning process, many students did not pay attention to the teacher when explaining and they were more cool to talk and have fun with their friends, some even walked to their other friends' seats. There are also many students who do not understand the material but are afraid to ask the teacher, so the learning process is not conducive at that time. The results of this study indicate that Picture Media Learning can improve mathematics learning outcomes, based on the results that continue to increase from the Pre-cycle the average value of students is 55.1 , with the percentage of completeness of 42.3%, and in the first cycle the average value of students is 71, 5, with the percentage of completeness of 73.1%. Likewise, in Cycle II, the average score of students was 83.5, with a mastery percentage of 88.5.